STRATEGI ZUKRI DALAM MEMPEROLEH SUARA PADA PEMILIHAN LEGISLATIF PROVINSI RIAU TAHUN 2014 - Lizbeth Lindrieny Lubis; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Strategy is a careful plan that organized and held by a candidate who has a purpose or target. The goal is what a candidate wants to achieve. In this case, especially is the target of vote’s support that manifested by the vote. A strategy should be able to describe the ways or steps to be taken.The legislative election is one of democracy action that held to elect the people’s representatives to achieve the political goal. In the legislative election that held on April 9th, 2014. People can elect and vote directly for a candidate. Zukri got the highest ballot / vote in six electoral districts, such as Pelalawan district and Siak district in the legislative election of Riau Province in 2014. Therefore, this research is trying to elaborate the strategy of Zukri clinched the votes / ballot in legislative election in 2014.Theories that used to explain the achievement are strategy theory and political marketing theory. These theories are used to review Zukri’s strategy in getting the votes and the achievement factors in getting the votes in VI electoral districts.Keywords: Strategy, Legislative Election